Application of antimalarial medications in the treatment of skin diseases - Katarzyna M. Chyl-Surdacka; Joanna Przepiórka-Kosińska; Agnieszka Gerkowicz; Dorota Krasowska; Grażyna Chodorowska (Przegląd Dermatologiczny, 2016)
Antimalarial drugs used in medicine for over 300 years, nowadays, due to their anti-inflammatory, immunomodulatory and antiproliferative photoprotective properties, are used in the therapy of many dermatologic and rheumatologic disorders. The efficacy of these medications is proven in systemic lupus erythematosus, rheumatoid arthritis, porphyria cutanea tarda, lichen planus, ulcerative stomatitis, sarcoidosis, and even alopecia areata. Chloroquine and hydroxychloroquine belong to a group of well-tolerated drugs that occasionally cause adverse effects, which include gastrointestinal disorders, retinopathy, cardiomyopathy, neuromuscular disorders, skin hyperpigmentations, and hematological disorders. Nevertheless, these drugs continue to be frequently applied, including for systemic diseases of connective tissue during pregnancy. However, the treatment must be monitored – periodic ophthalmologic examinations during therapy with chloroquine must be performed, especially during prolonged treatment with high doses of these drugs. The article discusses the mechanism of action, pharmacokinetics, indications and adverse effects of these medications.